Study on indoor air quality of a small office in a tropical country - Majid, S.A. (2013)
Recently, the importance of appropriate Indoor Air Quality (IAQ) attracts interests in health research area. The study of IAQ is important in office. Long term period exposure to poor IAQ level, can lead to discomfort and uneasy feeling and thus may affect productivity and quality of life. The objective of this work is to study the IAQ level in a small lecturer office of an educational building in Malaysia. Throughout this research, the IAQ of a selected lecturer office room was studied. The study involved measurements of indoor air temperature, relative humidity, and CO2 level. From the study, it was found that the level of CO2 temperature and humidity were always within the range of recommended by ASHRAE. Â© (2013) Trans Tech Publications, Switzerland.